Effects of SiC on the microstructures and mechanical properties of B4C–SiC–rGO composites prepared using spark plasma sintering. Issue 4 (April 2022) - Hu, Lanxin; Wang, Aiyang; Tian, Tian; Liu, Chun; Guo, Wenchao; He, Qianglong; Wang, Hao; Xie, Jingjing; Wang, Weimin; Fu, Zhengyi
Abstract: In this study, B4 C–SiC–rGO composites with different SiC contents were prepared by spark plasma sintering at 1800 °C for 5 min under a uniaxial pressure of 50 MPa. The effects of SiC on the microstructures and mechanical properties of the B4 C–SiC–rGO composites were investigated. The optimal values for flexural strength (545.25 ± 23 MPa) and fracture toughness (5.72 ± 0.13 MPa·m 1/2 ) were obtained simultaneously when 15 wt.% SiC was added to 5 wt.%–GO reinforced B4 C composites (BS15G5). It was found that SiC and rGO inhibited the grain growth of B4 C and improved the mechanical properties of the B4 C–SiC–rGO composites. The clear and narrow grain boundaries of rGO–B4 C and rGO–SiC, as well as the semi-coherent B4 C–SiC interface, indicated strong interface compatibility. The twin structures of SiC and B4 C observed in the composites improved their fracture toughness. Crack deflection and crack bridging caused by the SiC grains as well as rGO bridging and rGO pull-out were observed on the crack propagation path.